Pergulatan Indonesia membangun ekonomi : pragmatisme dalam aksi - Prawiro, Radius; Parera, Frans M. (Jakarta : Elex Media Komputindo, Kelompok Gramedia, 1998)
Author's account on Indonesian economic development, economic policy, public finance, etc. during his occupation as Director of Bank of Indonesia, Minister of Trade, Minister of Finance, etc., 1960-1998
Includes bibliographical references (p. 503-512) and index
Keywords: Economic stabilization -- Indonesia; Indonesia -- Economic conditions -- 1945-; Indonesia -- Social conditions